Ujjayi pranayama in systemic lupus women: randomized-controlled effect oncortisol, stress, depression, anxiety, and fatigue - Abdelhalim Elfahl, Ahmed Mohamed; Hossam El Ebrashy, Mariam; Mustafa Saleh, Marwa Shafiek; El Monem, Maha Abd (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The aim of this study was to investigate the effects of ujjayi pranayama on non-lethal problems and cardiorespiratory functions in women with systemic lupus erythematosus (SLE).Methods. This randomized controlled trial involved a home-based training of ujjayi pranayama for 6 weeks. Forty SLE womenwere randomly assigned to either the ujjayi-pranayama group (n = 20), who performed 30 min of ujjayi pranayama daily (15 minin the morning and evening), or the waitlist control group (n = 20). Various measures, including State-Trait Anxiety Inventory(STAI), cortisol, Stress Vulnerability Scale (SVS), Beck Depression Inventory II (BDI-II), Fatigue Severity Scale (FSS), PittsburghSleep Quality Index (PSQI), pulse rate (Pul-r), respiratory rate (Res-r), systolic blood pressure (SBPr), and diastolic blood pressure(DBPr) were assessed.Results. Significant reductions were observed via paired tests in Pul-r (75.95 ± 3.63 vs 72.95 ± 3.17; p < 0.001), Res-r (16.70 ±3.62 vs 14.80 ± 2.94; p < 0.001), SBPr (126.60 ± 4.75 vs 121.30 ± 4.30; p < 0.001), DBPr (82.15 ± 3.57 vs 78.05 ± 3.44; p < 0.001),PSQI (7.45 ± 1.27 vs 5.10 ± 1.20; p < 0.001), FSS (4.80 ± 1 vs 3.75 ± 1.11; p < 0.001), BDI-II (13.70 ± 2.77 vs 6.80 ± 1.50; p < 0.001),STAI (66.70 ± 4.72 vs 47.55 ± 6.15; p < 0.001), cortisol (8.51 ± 1.36 vs 6.34 ± 1.36; p < 0.001), and SVS (12.65 ± 1.78 vs 6.45 ± 1.57;p < 0.001) in the ujjayi pranayama group only.Conclusions. Ujjayi pranayama significantly improved non-lethal problems and cardiorespiratory functions in women withlupus.
Keywords: pranayama; stress; fatigue; anxiety; lupus